Pengaruh Rendam Kaki Air Hangat Terhadap Tekanan Darah pada Lansia Hiperten - Ayu Okta Viana; Irma Mustika Sari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Age is one of the factors that trigger hypertension that cannot be controlled, this causes more than 60% of the elderly to experience hypertension. One treatment that can be done to control blood pressure is to soak the feet in warm water. This study aims to determine the effect of soaking feet in warm air on blood pressure in the elderly with hypertension. Using quantitative research methods, the method used was pre-experimental with one group pre-test-post-test design, the research sample used purposive sampling with 20 elderly people, the research instrument used an observation sheet and a sphygmomanometer. The results of the univariate analysis of systolic blood pressure before the intervention were 159 mmHg and diastolic was 90 mmHg, the average systolic blood pressure after the intervention was 139 mmHg and diastolic 80 mmHg. The results of the Wilcoxon test bivariate analysis showed that systolic blood pressure p = 0.000 <0.05 and diastolic blood pressure p = 0.000 <0.05. The conclusion from the results obtained is that there is an effect of warm air foot soak on blood pressure in hypertensive elderly in Sambilenguk Hamlet.